CCR2 and TLR3: noninvasive macrophage-associated biomarkers of acute renal transplant rejection - Shili Wang; Xingyu Pan; Jinpu Peng; Moudong Wu; Xiong Zhan; Wei Wang; Guohua Zhu; Nini An; Jun Pei (Renal Failure)
Background The study aims to investigate the role and significance of macrophage-related genes in peripheral blood during acute renal transplant rejection.Methods Based on the dataset GSE15296, differential genes (DEGs) were intersected with macrophage-associated genes (MAGs), which defined as macrophage-associated genes (DEMAGs). Subsequently, GO and KEGG enrichment analyses were performed on DEMAGs. The PPI protein interaction network and machine learning were applied to identify Hub genes, which were also validated by GSE46474, an external validation set. We constructed a rat model of acute rejection of kidney transplantation and sequenced the transcriptome of the serum, and using the sequencing results, we analyzed the expression levels of the Hub gene. Then, a correlation analysis was carried out based on the Hub genes and different immune cell infiltration levels. Finally, GRNdb, miRDB, and GeneCards databases were applied to study the transcription factors, miRNAs, and regulatory drugs of Hub genes, respectively.Results The results of the Cibersort analysis revealed that M2-type macrophages were expressed higher in the Normal group. In addition, the results of the correlation analysis suggested that the expressions of Hub genes were negatively correlated with M1-type macrophages and positively correlated with M2-type macrophages.Conclusion A diagnostic model of the macrophage-associated acute renal transplant rejection in peripheral blood was constructed based on CCR2 and TLR3, which can accurately diagnose the biological alterations of acute kidney transplant rejection. Meanwhile, these two Hub genes may become potential therapeutic targets in acute rejection of kidney transplantation.